Ethics of agriculturalists - Paudel, MN (Agronomy Journal of Nepal, 2013)
Agronomy is the mother of agriculture and it is also synonymous to agricultur as well. Therefore, agronomy in general term in this article not only limits to the core discipline of agronomy and agronomists but also it entails the whole sphere of agriculture and agriculturists as well. Nonetheless, readers are humbly urged to take ethics of agronomists as the ethics of agriculturists for this is the agronomy journal’s article which is meant for agronomists in general perspectives. It has been mentioned in this paper that what are the ethical boundaries of agriculturists in professional capacity. The paper also describes what the ethical issues with respect to agronomist as a researcher and extensionist are entailing while executing their duty. Pressures have been brought to bear upon farming and those who serve it in any capacity to widen the list of tasks to which agriculture should be devoted. At one time, the role of agriculture was to produce food, but now many people expect agriculture to be carried out in an environmentally friendly way that maintains the rural economy. We now speak of multifunctional agriculture. One tool sometimes used to press those demands is an appeal to ethics. This appeal can appear to suggest that agriculturalists have been ethically negligent. Every agricultural ethicist knows by experience how poorly received that suggestion is. Agriculture is a vocation or profession that prides itself on the unquestionable value, even nobility, of its work. Whereas agronomists should be engaged for number of works in day to day life involving social justification in farming, soil fertility and sustainability, soil conservation, rural living condition, farming and environment, healthy and nontoxic food production to the masses in an affordable manner, and so on and so forth. Above all, there is a big morale of agriculturist to save Mother Nature for our future generation tailored with multinational companies, engaged in agriculture, which have big say in generating and disseminating agro-technologies which are mooted to profit making and patenting agro biodiversity. This paper sheds lights in all such issues and aware agriculturists if it is being done ethically on the part of agriculturists/agronomists. Also the paper cites what are the ethical concerns of agriculturists to make their profession ethically sound that include honesty, integrity, fairness, and service to the clienteles in question. DOI: http://dx.doi.org/10.3126/ajn.v2i0.7516 Agronomy Journal of Nepal (Agron JN) Vol. 2: 2011 pp.1-11